Morphometric analysis of biotypes A, B, and Q of Bemisia tabaci from the state of Sinaloa, Mexico - Carnero-Avilés, Leslie; Cerna-Chàvez, Ernesto; Ochoa-Fuentes, Yisa M. (Ecosistemas y Recursos Agropecuarios, 2021)
The whitefly Bemisia tabaci is a complex of species of importance for the agricultural industry due to the damage it causes by more than 50% in vegetable crops. In order to relate the morphological variations with the biotypes of B. tabaci, three samples of populations were collected from the municipalities of Mocorito, Elota and Culiacán of the State of Sinaloa, Mexico, and were genetically identified using the gene (mtCO-1) like biotypes A, B and Q respectively. The morphometric study was carried out with 30 individuals of each biotype and the data obtained were subjected to an analysis of variance and Tukey's test. It was obtained that biotype B presented greater length and width in all instars, followed by biotype A with statistically significant differences of the 2nd, 3rd instar and "pseudopupa" between the biotypes, finally, biotype Q exhibited the smallest dimensions.